PENERAPAN LATIHAN PAPAN PANTUL UNTUK MENINGKATKAN KEAKTIFAN SISWA DAN KETERAMPILAN TEKNIK DASAR PASING BAWAH PERMAINAN BOLA VOLI (Studi pada Mata Pelajaran PJOK Kelas VI SD Negeri 9 Pagar Alam) - Suwarno Suwarno; Bayu Insanistyo (DIADIK, 2021)
This study aims to  describe the implementation of the bounch board exercise to increase student activity;to describe the implementation of the bounce board exercise in improving the basic technique of under pasing skill of volleyball; to describe the effectiveness of the application of the bounce board exercise in increase the basic technique of under pasing skills in the subjects of sports and Health Education.This type of research is classroom action research (CAR) and quasi-experimental. The research subjects were sixth grade students of SD Negeri 9 Pagar Alam Data collection techniques in this study used observation sheets to measure the learning process and creative thinking abilities of students and tests to measure learning achievement. While the data analysis used the average score analysis, normality test and homogeneity test and t-test In the first cycle the average score of student activeness is 2.41 the average score of underpasing skills is 66.67 classical completeness 50%, the second cycle the average student activeness is 2.95 the average of underpasing skills is 73.92 with 70 classical completeness , 83%, in the third cycle the average student activeness was 3.40 the average of underpasing skills was 83.71 with classical completeness 95.83%. This study resulted in the following conclusions: (1) the implementation of the bounch board exercise can increase student activity; (2) the implementation of of the bounce board exercise can improve the basic technique of under pasing the volleyball game; (3) the implementation of the bounce board exercise is effective to improve the basic technique of pasing under skills in volleyball games